Influences of microRNA-451 on the expression of HMGB1 in myocardial cells and its mechanism in ischemia-reperfusion injury: HMGB1 in myocardial cells and ischemia-reperfusion - Qiu, Ruiye; Zhang, Yajuan; Li, Jun; Wu, Jun; He, Ruifeng (Cellular and Molecular Biology, 2023)
This work aimed to understand the underlying mechanism of micro-ribonucleic acid (MicroRNA) (miR)-451 in ischemia-reperfusion injury (IRI) and the influences of miR-451 on high mobility group box 1 protein (HMGB1) in myocardial cells, 30 specific pathogen-free (SPF) male rats were selected and randomly rolled into 5 groups, which were a sham operation control (Control), an ischemia-reperfusion (I/R), aI/R+Ad-GFP, amiR-451 up-regulation (I/R+Ad-miR-451), and a miR-451 down-regulation groups (I/R+Ad-asmiR-451). There were 6 cases in each group. Myocardial cell apoptosis, the contents of serum lactic acid dehydrogenase (LDH), creatine kinase (CK), and malondialdehyde (MDA), the activity of superoxide dismutase (SOD), and the expressions of miR-451 and HMGB1mRNA were detected. Relative to those in I/R and I/R+Ad-GFP groups, the expressions of CD3+, CD4+, and CD4+/ CD8+ in I/R+Ad-miR-451 group reduced (P<0.05). The expressions of serum LDH and CK decreased (P<0.05). In contrast, MDA content and SOD activity enhanced (P<0.05). HMGB1 and Cleaved-caspase3 declined (P<0.05). Besides, miR-451 improved while the expression of HMGB1mRNA significantly reduced (P<0.05). miR-451 can regulate the expressions of HMGB1mRNA and its protein at the transcriptional level. miR-451 up-regulation can inhibit HMGB1 expression, relieve IRI, and protect myocardial cells, which may be achieved by improving oxidative stress injury and inhibiting cell apoptosis.